Implementation of Online Learning Using Online Media, During the Covid 19 Pandemic - Nanda Saputra; Nurul Hikmah; Via Yustitia; Miswar Saputra; Abdul Wahab; Junaedi Junaedi (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2021)
Due to outbreak of the Covid 19, the implementation of education and learning has extremely changed. Face to face meetings as a conventional learning is no longer conducted, in contrast, online learning is more often employed. Thus, a solution to this problem is required to respond to this problem. Online learning is an alternative that can overcome this problem. The purpose of this research is to get a reflection of the implementation of online education by using online media to reduce the outbreak of Covid-19 in universities. The research subjects were PGMI students who were interviewed through Zoom Cloud Meeting to collect the data. The data analysis employed was an interactive analysis method Miles & Huberman. The results of the research showed that: (1) the students had already had the basic facilities needed to explore online education; (2) the online education was flexibly being implemented, encouraging learning independently, motivating to learn more actively; and (3) long distance education urges the students to get used to social distancing attitude and minimizes crowds to reduce the outbreak of Covid-19 in institutions tertiary. The lack of supervision of students, lack of internet signals in remote areas, and high quota payments were challenges in online education. The increasing of independent learning, attention, motivation, and the courage to express ideas and problems was another advantage of online education.